UPAYA OPTIMALISASI POTENSI DESA CIBULUH MELALUI KEGIATAN PENGABDIAN - Amelia Limijaya, Dkk (JURNAL PRODIKMAS Hasil Pengabdian Kepada Masyarakat, 2017)
The devotion activities undertaken in Cibuluh Village is one of the efforts to support the Nawa Cita program proclaimed by the government, especially the 3rd and 5th points, which is about building Indonesia from the periphery by strengthening the regions and villages within the framework of the unitary state and improving quality of life of Indonesians through the improvement of the quality of education and training, and in line with UNPAR's vision to "Become a humanum academic community that develops local potentials to the global level for the enhancement of human dignity and the integrity of creation". Cibuluh Village is a village located in Subang Regency, West Java, and has a number of potentials that can be developed, especially in the field of tourism and economy. The scope of this devotion consists of (1) the organization of financial recording training for UMKM and family entrepreneurs (2) proposing a number of points to maximize tourism potential owned by the village (3) discussion planning and further programming related to the preparation of the village strategic plan for the utilization of funds villages can be more optimal. It is expected that this devotional activity can contribute to the progress of Cibuluh Village and support the development of the regions and villages in Indonesia for mutual progress.